IMPACT OF GRID CONNECTED PHOTOVOLTAIC SYSTEM UNDER DIFFERENT WEATHER CONDITIONS AND LOAD TYPE - Asma, Rebai; Zoubir, Zahzouh; Saliha, Boulahchiche (Journal of Applied Engineering Science, 2023)
Electricity distribution managers are continuously under pressure to expand their grids to cope with load growth and properly supply their consumers. To achieve these objectives, it is necessary to provide an acceptable climate for the entry of solar resources and innovative operating practices. This work focuses on a study the impact of the insertion of photovoltaic energy into the low voltage distribution grid. We have shown the impact of weather conditions on the power injected into the grid, the impact of using a single-phase inverter with a TT-neutral regime, the flow of active and reactive bidirectional power to the point of common coupling PCC, and the impact of a grid connected photovoltaic system under different weather conditions and load types. This study was carried out using the Matlab Simulink environment for modeling and simulation of a single-phase system with a 3,5kW transformer inverter and the results show the impact of PV system integration on the overall and individual harmonic level of voltage and current considering several scenarios (variable solar irradiation, variable types of loads),the presence of filters such as the inductor and the capacitor in series or in parallel plays very important role on the improvement in the disturbance of the quality of the current and the tension.
Keywords: PV system, energy quality, PCC, LV network, harmonics